Subjective assessment of the state of health of teachers with different levels of occupational burnout in conditions of social isolation and martial law (Environment & Health, 2024)
The aim of the study is to analyze data on the state of health of teachers with different levels of occupational burnout who were in different social conditions of life (social isolation and martial law).Materials and methods. To achieve the goal, the method of V. V. Boiko «Diagnostics of the level of emotional burnout» (1998) and a specially developed questionnaire «Subjective assessment of the state of health, life activities and working conditions of teachers» were used, with the help of which an anonymous survey was conducted general secondary education institutions in the city of Sumy during the period of social isolation due to the COVID-19 pandemic caused by the SARS-CoV-2 coronavirus in 2021 (85 people) and during martial law in April 2023 (106 people).Results. The proportion of the group of teachers with a low level of occupational burnout increased and was 2.22 times higher than the similar group of teachers during the period of social isolation (30.97±3.35)%, t=8.04, p≤0.001), which may indicate a possible decrease in the influence of professional stressors and an actualization of the feeling of uncertainty, constant anxiety, fear for one’s own life and the lives of loved ones, which is due to the military situation in the country.In conditions of social isolation caused by the COVID-19 pandemic, average (48.24±3.36)% t=9.54, p≤0.001) and low (41.18±3.31)% t=7.83, p≤0.001) levels of occupational burnout prevailed. Under the conditions of martial law, the manifestations of occupational burnout changed: the proportion of the group of teachers with a low level of occupational burnout increased and was 2.22 times higher than the similar group of teachers during the period of social isolation (30.97±3.35)%, t=8.04, p≤0.001), which may indicate a possible decrease in the influence of professional stressors and an actualization of the feeling of uncertainty, constant anxiety, fear for one’s own life and the lives of loved ones, which is due to the military situation in the country.If during the period of isolation caused by the COVID-19 pandemic, a high level of occupational burnout significantly prevailed among teachers under the age of 40 (55.56±5.38)%), then during the period of martial law, a high level of occupational burnout was mainly registered among teachers of the older age group (up to 50 – (42.86±4.81)%).In general, (76.02±3.09)% of the surveyed teachers defined their health status as satisfactory, (16.29±2.67)% as unsatisfactory, and only (7.69±1.93)% of respondents as excellent. Among the interviewees in the group with unsatisfactory self-assessment of health, teachers of the age groups «under 50» and «over 50» predominated (36.11±3.47)% and (30.56±3.33)%, respectively) compared to the groups «up to 30» – (8.33±1.99)% and «up to 40» – (25.00±3.13)%, which can be explained by the natural accumulation over the years of functional abnormalities and chronic pathology. The leading complaints, regardless of social conditions and levels of occupational burnout, were complaints of headaches, palpitations, sleep disturbances, and increased blood pressure.Conclusions. The established results of the study require further improvement of the assessment of the components of mental health among teaching staff in conditions of martial law and the development of hygienic recommendations for the prevention of occupational burnout in various social conditions of the labor process.
Keywords: occupational burnout; mental health; teachers; state of health; pandemic; martial law